Differentiation of Transformed Bipolar Disorder From Unipolar Depression by Resting-State Functional Connectivity Within Reward Circuit - Shi, Jiabo; Geng, Jiting; Yan, Rui; Liu, Xiaoxue; Chen, Yu; Zhu, Rongxin; Wang, Xinyi; Shao, Junneng; Bi, Kun; Xiao, Ming; Yao, Zhijian; Lu, Qing (Frontiers in Psychology, 2018)
Previous studies have found that neural functional abnormalities detected by functional magnetic resonance imaging (fMRI) in brain regions implicated in reward processing during reward tasks show promise to distinguish bipolar from unipolar depression, but little is known regarding resting-state functional connectivity (rsFC) within reward circuit. In this study, we investigated neurobiomarkers for early recognition of bipolar disorder (BD) by retrospectively comparing rsFC within reward circuit between unipolar depression (UD) and depressed BD. Sixty-six depressed patients were enrolled, and none of whom ever experienced any manic/hypomanic episodes before baseline. Simultaneously, 40 matched healthy control (HC) were also recruited. Neuromaging data of each participant was obtained from resting-state fMRI scan. Some patients transformed into bipolar disorder (tBD) during the follow-up period. All patients were retrospectively divided into two groups (33 tBD and 33 UD) according to the presence or absence of mania/hypomania in the follow-up. Rs-FC between key regions of reward circuit was calculated and compared among groups. Results showed decreased rsFC between the left ventral tegmental area (VTA) and left ventral striatum (VS) in tBD group compared with UD group, which showed good accuracy in predicting diagnosis (tBD vs. UD) according to receiver operating characteristics (ROC) analysis. No significant different rsFC was found within reward circuit between any patient group and HC. Our preliminary findings indicated that bipolar disorder, in early depressive stage before suffering from mania/hypomania attack, already differs from unipolar depression in reward circuit of VTA-VS functional synchronicity during resting-state.